PENETAPAN HARGA POKOK PRODUK HORTIKUlTURA (Kasus di Agri Wira Pratama) - Damaidjati, Effi (MAPETA, 2000)
Determination of base price sale was very important for every commercial business, including horticutture company, because determination of base price will influence sale price of that product Sale pnce must be determined prerisely; because it will influence company benefits and consumer awake to buy that product. Mistaken in determining sale price will cause neither company loosing nor consumer will move to find another product. From BEP counting, balance point for that comodity it cellerry and leek; more diminish; It means that Infact sale price still can diminish; without causing company loosing. It must be done by company In facing another company